Le touriste malgré lui : John Edgar Wideman et la Martinique - Michel Feith (Revue LISA)
African-American writer John Edgar Wideman chose the French Caribbean island of Martinique as setting and object of his travel narrative for his dual relationship to the place. He is both an outsider—in matters of language and citizenship—and an insider—as a member of the African diaspora in the Americas, and through his French girlfriend. To go to an alien nation is to experience alienation, hopefully leading to “the clarifying distance and difference” that allows a novel outlook on one’s own identity. On the “realistic” side, the writer imagines himself as a respectful wanderer, poles apart from the colonizer or the plantation owner. Yet, tourism can also be a late outpost of slavery, “stealth” having replaced strength as a tool of domination. Moreover, in a striking mirroring of center and periphery, natives and French people from the Métropole envy each other, in a game of musical chairs that is also a fantasy of freedom. To escape from this uncanny state of historical alienation, one has to reinvent the island. To think different is to make things different. This is why travel writing is more than “non fiction”. Love, dreams and stories are also factories of the real. The book does not only represent the island, it is the island: an islanded text, an intertextual archipelago. The work works itself out in a constant to-and-fro movement between a U.S. minority perspective and the angle of vision of Martiniquan writers. The place becomes an eerie compound of the strange and familiar, and the writing ends up embodying the “Poetics of Relation” proposed by Edouard Glissant.